2z+6=4z-3

Simple and best practice solution for 2z+6=4z-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2z+6=4z-3 equation:


Simplifying
2z + 6 = 4z + -3

Reorder the terms:
6 + 2z = 4z + -3

Reorder the terms:
6 + 2z = -3 + 4z

Solving
6 + 2z = -3 + 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
6 + 2z + -4z = -3 + 4z + -4z

Combine like terms: 2z + -4z = -2z
6 + -2z = -3 + 4z + -4z

Combine like terms: 4z + -4z = 0
6 + -2z = -3 + 0
6 + -2z = -3

Add '-6' to each side of the equation.
6 + -6 + -2z = -3 + -6

Combine like terms: 6 + -6 = 0
0 + -2z = -3 + -6
-2z = -3 + -6

Combine like terms: -3 + -6 = -9
-2z = -9

Divide each side by '-2'.
z = 4.5

Simplifying
z = 4.5

See similar equations:

| =2u^10v^9w^8*w*9v^2*4u^9 | | (2m^2*n^-2*p^0/m^-2)^3= | | x^2*x^9= | | 0.3(0.2x-1)=0.4(0.5x-1) | | 2/5-7/20x=2 | | 3x-2=1/2=x/3 | | 5h+2(1-h)=-5 | | -4.3-k=-4.57 | | 16-6r=25-3r | | 4x-0.6-1.6x+2.9x+4= | | 6x+8=8x-3 | | -17.2=x-7.7 | | 6x+24+2x=68 | | n-6=n-8 | | 4-y/-17 | | 9+(-16)=-1 | | V/4=3/4 | | 2=b/8 | | 13x+88=107 | | f(x)=5x^2-19x-4 | | 6x-4=10+x | | 6x^2y^3/12x^3y | | x+5=-25 | | B+42=100 | | 8x^2-(-2-1)x+32=0 | | 8x^2-(2-1)x+32=0 | | 2a-9+a=90 | | 3x^2-x+-3=0 | | 3x^2-x+-1=0 | | -11+10x(p+10)=4-5(2p+11) | | 20-2x=-4+4x | | 37-7x=10+2x |

Equations solver categories